Small beer? peer‐to‐peer lending in the craft beer sector. (13th January 2019) - Mac an Bhaird, Ciarán; Owen, Robyn; Dodd, Sarah Drakopoulou; Wilson, Juliette; Bisignano, Angelo
Abstract: Peer‐to‐peer lending has advantages of ease of access to finance, timely and efficient delivery of funding and is particularly beneficial at a specific time in the lifecycle of the firm.